2014
DOI: 10.1177/1534650114552556
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Anxious Youth With a Physical Disability

Abstract: Cognitive-behavioral therapy (CBT) is the first-line psychological intervention for youth with an anxiety disorder. Despite the prevalence of anxiety in youth with physical disabilities, the application and evaluation of CBT for such youth is sparse. The current report illustrates ways to adapt, implement, and evaluate CBT for youth with anxiety and a physical disability describing "Olivia," a 12-year-old Caucasian female with generalized anxiety disorder, separation anxiety disorder, panic attacks, and cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…Study sample sizes ranged from one to 49, with mean ages ranging from 6.87 to 15.9 years. Conditions studied included CP ( 36 , 39 , 41 ) and childhood onset ABI ( 33 35 , 37 , 40 , 42 , 43 ), consisting of TBI, with only one study having a variety of ABI conditions ( 40 ). No studies reported on interventions for SB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study sample sizes ranged from one to 49, with mean ages ranging from 6.87 to 15.9 years. Conditions studied included CP ( 36 , 39 , 41 ) and childhood onset ABI ( 33 35 , 37 , 40 , 42 , 43 ), consisting of TBI, with only one study having a variety of ABI conditions ( 40 ). No studies reported on interventions for SB.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly identified psychological interventions used with individuals with childhood onset ABI and CP were acceptance and commitment therapy (ACT) ( 34 , 37 , 38 , 40 ), psychotherapy ( 39 , 41 ), and CBT ( 33 , 35 , 36 , 42 , 43 ), in combination with components of family therapy ( 34 ), psychoeducation ( 33 , 36 , 43 ), and Stepping Stones Triple P (SSTP) ( 40 ). Studies reporting on ACT were limited to individuals with childhood onset ABI, while studies investigating the use of psychotherapy only included individuals with CP.…”
Section: Resultsmentioning
confidence: 99%
“…Ideas generated for challenge cards were drawn from an extensive literature review, including previously published treatment manuals for youth anxiety (e.g., Albano & DiBartolo, 2007; Kendall & Hedtke, 2006), published articles on the application of exposure for youth (e.g., Kendall et al, 2006; Peterman, Read, Wei, & Kendall, 2015), published case studies (e.g., Heyne, Sauter, Ollendick, Van Widenfelt, & Westenberg, 2014; Peterman, Hoff, Gosch, & Kendall, 2015), in conjunction with clinical expertise. Recognizing that some exposures conducted within anxiety specialty clinics (e.g., going to the zoo to see or hold a snake, having a phlebotomist attend a therapy session to address blood-injection-injury fears) may not be feasible within the confines of an under-resourced clinic setting, READY distinguishes exposures that can be done without any additional materials or confederates from those that require additional materials.…”
Section: Methodsmentioning
confidence: 99%
“…Cards can be used to facilitate hierarchy building by asking clients to arrange challenges in order from easiest to hardest. Given emerging research suggesting that it may not be necessary to engage in exposures in a linear fashion from the bottom of the hierarchy to the top (Craske et al, 2014; Peterman et al, 2015), challenge cards do not need to be used in a particular order. For example, clinicians can select a handful of appropriate level exposure exercises that could potentially be completed in a single session and have the patient select one at random to complete.…”
Section: Methodsmentioning
confidence: 99%
“…For individuals with CP who have such issues, clinicians will need to provide an appropriate, evidence-based psychological treatment. Along these lines, Peterman, Hoff, Gosch, and Kendall (2015) described the effective treatment of anxiety in a 12-year-old girl with CP. The treatment, which involved 24, 1-hr sessions using an age-adapted version of cognitive-behavioral therapy, resulted in marked reductions in anxiety symptoms.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%